PROFESSIONAL EXAMINATIONS. - Chamberlain, Henry T. (The Accounting Review, 1941)
The article focuses on professional examinations for students of accountancy. The following problems were prepared by the Board of Examiners of the American Institute of Accountants which were presented on November 13, 1941, as the first half of the Chartered Public Accountants (CPA) Examination in accounting theory and practice. The examinees were allowed six hours to solve these problems and weights were assigned as follows: problem 1, 12 points; problem 2,4 points; problem 3, 16 points; problem 3,16 points; problem 4, 14 points; problem 5, 6 points. A suggested time schedule is given below; Problem 1,60 minutes; Problem 2,15 minutes; Problem 3,120 minutes; Problem 4,90 minutes; Problem 5, 30 minutes. A depreciation schedule for auto trucks of a company was requested by an income-tax revenue agent soon after December 31, 1940, showing the additions, retirements, depreciation and other data affecting the taxable income of the company in the four-year period 1937 to 1940 inclusive.